2005
DOI: 10.1529/biophysj.104.058750
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydrocortisone on the Mechanical Properties of the Cerebral Endothelium In Vitro

Abstract: Cerebral endothelial cells accomplish the barrier functions between blood and brain interstitium. Structural features are the tight junctions between adjacent endothelial cells and the formation of marginal folds at the cell-cell contacts. The glucocorticoid hydrocortisone (HC) has been reported to enforce the blood-brain-barrier in vitro measurable by an increase of the transendothelial electrical resistance. This study shows the impact of HC on the mechanical and morphological properties of confluent cell la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 37 publications
3
27
0
Order By: Relevance
“…This is in line with a study reporting increased F-actin assembly at the cell periphery in Chinese hamster ovary cells under hyperosmotic stress in order to withstand osmotic shrinkage (Di Ciano et al, 2002). In brain capillary endothelial cells an increased perijunctional F-actin ring that formed in response to hydrocortisone incubation caused a higher cell rigidity and higher TER (Schrot et al, 2005). Indeed it was shown that the perijunctional F-actin ring is not a static structure but undergoes continuous F-actin depolymerization and repolymerization ('treadmilling').…”
Section: Cortisol Increased F-actin Under Hyperosmotic Stresssupporting
confidence: 91%
“…This is in line with a study reporting increased F-actin assembly at the cell periphery in Chinese hamster ovary cells under hyperosmotic stress in order to withstand osmotic shrinkage (Di Ciano et al, 2002). In brain capillary endothelial cells an increased perijunctional F-actin ring that formed in response to hydrocortisone incubation caused a higher cell rigidity and higher TER (Schrot et al, 2005). Indeed it was shown that the perijunctional F-actin ring is not a static structure but undergoes continuous F-actin depolymerization and repolymerization ('treadmilling').…”
Section: Cortisol Increased F-actin Under Hyperosmotic Stresssupporting
confidence: 91%
“…However, addition of HCT did not improve the tightness of RBE4 cell monolayers despite the fact that this approach was successful in primary cultures of various species. 19 The reason for the failure could be the presence of serum in the culture medium because HCT induces a greater increase in transendothelial electrical resistance in the absence of serum. It has been suggested that some modulators in serum affect HCT-triggered cellular signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…16 Hydrocortisone (HCT) has also been included in the medium as it reportedly improves the tightness of the paracellular pathway in primary cultured brain capillary endothelial cell monolayers. [17][18][19] Glucocorticoids increased vascular endothelial-cadherin expression and caused cytoskeletal rearrangement to improve the barrier properties of microvascular brain endothelial cells. 18 One objective of the present study was to compare these two strategies to determine which would be better to improve the tightness of RBE4 cell monolayers.…”
Section: Introductionmentioning
confidence: 99%
“…Cell growth, proliferation, migration, adhesion, and differentiation are highly dependent on and regulated by cellular mechanical properties (Nagayama et al, 2001;Laurent et al, 2005). It is well known that eukaryotic cells respond to external mechanical stimuli by adjusting their biochemical and biomechanical properties (Lekka et al, 2001;Schrot et al, 2005;Pesen and Hoh, 2005). Therefore, a thorough understanding of cell mechanical parameters would be important in the development of cell biology, medicine, and tissue engineering.…”
Section: Mechanical Properties Of Lymphocyte and Jurkat Cellsmentioning
confidence: 99%